2021
DOI: 10.1027/0227-5910/a000707
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Behaviors in the Ghana Police Service

Abstract: Abstract. Background: Despite recent media reports showing disturbing trends of police suicides in Ghana, no published studies are available from the country. Aims: We sought to estimate the prevalence and describe some of the correlates of suicidal behaviors among police officers in the Greater Accra Region of Ghana. Method: We surveyed a convenience sample of 268 police officers, using the Suicide Behavior Questionnaire-Revised to assess suicidal ideation, planning, threat, and attempt. Results: Whereas life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Thus, in the current study, suicidal behaviour risk was binary, high suicidal behaviour risk vs. low suicidal behaviour risk. In Ghana, the SBQ-R has a satisfactory internal consistency (Cronbach's alpha = 0.78) among both adolescents and adults (Adjorlolo, Anum, & Amin, 2020;Quarshie, Cheataa-Plange, Annor, Asare-Doku, & Lartey, 2019;Quarshie, Odame, & Annor, 2020). The Cronbach's alpha score in the current study was 0.71.…”
Section: Socio-demographic Characteristicsmentioning
confidence: 52%
“…Thus, in the current study, suicidal behaviour risk was binary, high suicidal behaviour risk vs. low suicidal behaviour risk. In Ghana, the SBQ-R has a satisfactory internal consistency (Cronbach's alpha = 0.78) among both adolescents and adults (Adjorlolo, Anum, & Amin, 2020;Quarshie, Cheataa-Plange, Annor, Asare-Doku, & Lartey, 2019;Quarshie, Odame, & Annor, 2020). The Cronbach's alpha score in the current study was 0.71.…”
Section: Socio-demographic Characteristicsmentioning
confidence: 52%
“…Findings also suggested that marital status modified the association between depression scores and suicidal ideation in women officers, with a notably stronger association in single women officers than in married women officers Subordinate theme 2 -job dissatisfaction. Partly stemming from burnout, five independent studies found that a low sense of job satisfaction or job dissatisfaction showed statistically significant associations with suicidal ideation (Berg et al 2003;Burke and Mikkelsen 2007;Meyer et al 2003;Quarshie et al 2021;Rothman and Strijdom 2002). More specifically, Quarshie et al (2021) observed that officers who reported low levels of job satisfaction were at an increased risk of experiencing suicidal ideation during the previous 12 months.…”
Section: Same As Abovementioning
confidence: 99%
“…Partly stemming from burnout, five independent studies found that a low sense of job satisfaction or job dissatisfaction showed statistically significant associations with suicidal ideation (Berg et al 2003;Burke and Mikkelsen 2007;Meyer et al 2003;Quarshie et al 2021;Rothman and Strijdom 2002). More specifically, Quarshie et al (2021) observed that officers who reported low levels of job satisfaction were at an increased risk of experiencing suicidal ideation during the previous 12 months. The researchers theorised that this finding should be expected given that "low job satisfaction may be a response to negative work experiences and unfavourable work characteristics, which can undermine the psychological health of police officers" (Quarshie et al 2021, p. 198).…”
Section: Same As Abovementioning
confidence: 99%
See 2 more Smart Citations